Greenflation? - Conny Olovsson; David Vestin (Sveriges Riksbank, 2023)
What are the real and nominal implications of a green transition to a state with sustainable energy production, and how should monetary policy react during such transition? Using a New-Keynesian model with an energy and a goods sector, we show that a green transition requires the relative price of energy to increase and the relative price of goods, the marginal cost of production, and the real wage to fall. We prove analytically that if energy is not used in production and nominal wages and goods prices are rigid, a flexible energy price and a monetary policy rule that sees through energy-price changes are sufficient for replicating the flex-price economy. If energy is used in production there will be deviations from efficiency but because energy's share of income is small, these deviations are marginal unless the increase in the carbon tax is aggressive and/or monetary policy ill suited. During the green transition, it is optimal for monetary policy to see through the increasing energy prices and focus on core inflation. The result is a modest increase in CPI.
Keywords: E52; E58; Q43; 330; Inflation; green transition; monetary policy; climate change